-6(b-4)=33-3b

Simple and best practice solution for -6(b-4)=33-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(b-4)=33-3b equation:


Simplifying
-6(b + -4) = 33 + -3b

Reorder the terms:
-6(-4 + b) = 33 + -3b
(-4 * -6 + b * -6) = 33 + -3b
(24 + -6b) = 33 + -3b

Solving
24 + -6b = 33 + -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
24 + -6b + 3b = 33 + -3b + 3b

Combine like terms: -6b + 3b = -3b
24 + -3b = 33 + -3b + 3b

Combine like terms: -3b + 3b = 0
24 + -3b = 33 + 0
24 + -3b = 33

Add '-24' to each side of the equation.
24 + -24 + -3b = 33 + -24

Combine like terms: 24 + -24 = 0
0 + -3b = 33 + -24
-3b = 33 + -24

Combine like terms: 33 + -24 = 9
-3b = 9

Divide each side by '-3'.
b = -3

Simplifying
b = -3

See similar equations:

| -3n+6-n=-42 | | (4x-1)(x+5)=0 | | -4x+28y=12 | | -5y-13=7-15y | | 2x-17=37 | | -3n-13+2n=-24 | | x^2+2x-298=0 | | 4n+5-6n=-17 | | -6x+37=7 | | 6x+50=8 | | 31-5k=17 | | 9x+62=-10 | | 62=8x+2(-1+4x) | | -5-(15y+-1)=2(7y+-16)-y | | 6-2(m+3)=8 | | y^2+12y+68=0 | | 5+1.5y=.375y+6 | | -4=3m+5 | | 7+2r=7 | | 8x+32=9x+36 | | 3(x+2)=5(2x+1) | | x^2+28x-480=0 | | x^3+3x^2-4x-12= | | 2.7=1.3-2d | | 3(4x-1)=4-2(5-3x) | | 3x^2+13x-16=0 | | 4(3x+2)=5(2x+1) | | -4(14-x)+14(2)= | | 9x^3+x^2-8x-9=0 | | 3y+4y-14=0 | | 64+3x=5x+43 | | -15+3x=0 |

Equations solver categories